Effects of Multispecies Probiotic on Intestinal Microbiota and Mucosal Barrier Function of Neonatal Calves Infected With E. coli K99 - Wu, Yanyan; Nie, Cunxi; Luo, Ruiqing; Qi, Fenghua; Bai, Xue; Chen, Hongli; Niu, Junli; Chen, Chen; Zhang, Wenju (Frontiers in Microbiology, 2022)
Altered gut microbiota are implicated in inflammatory neonatal calf diarrhea caused by E. coli K99. Beneficial probiotics are used to modulate gut microbiota. However, factors that mediate host-microbe interactions remain unclear. We evaluated the effects of a combination of multispecies probiotics (MSP) on growth, intestinal epithelial development, intestinal immune function and microbiota of neonatal calves infected with E. coli K99. Twelve newborn calves were randomly assigned as follows: C (control, without MSP); D (E. coli O78:K99 + gentamycin); and P (E. coli O78:K99 + supplemental MSP). All groups were studied for 21 d. MSP supplementation significantly (i) changed fungal Chao1 and Shannon indices of the intestine compared with group D; (ii) reduced the relative abundance of Bacteroides and Actinobacteria, while increasing Bifidobacteria, Ascomycetes, and Saccharomyces, compared with groups C and D; (iii) improved duodenal and jejunal mucosal SIgA and total SCFA concentrations compared with group D; (iv) increased relative ZO-1 and occludin mRNA expression in jejunal mucosa compared with group D; and (v) enhanced intestinal energy metabolism and defense mechanisms of calves by reducing HSP90 expression in E. coli K99, thereby alleviating the inflammatory response and promoting recovery of mucosal function. Our research may provide direct theoretical support for future applications of MSP in ruminant production.